2015
DOI: 10.1007/s40299-015-0256-z
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning: An Approach to Promote Energy Literacy Among Secondary School Students

Abstract: Globalization, rapid industrial development, and tremendous population growth have significantly increased the demand for energy. Sustaining the energy supply requires that society be energy literate. Existing studies on secondary school students' energy literacy suggest that effective teaching approaches can enhance energy literacy. This quasi-experimental study was designed to test the null hypotheses that project-based energy learning does not enhance knowledge, attitudes, behavior, and beliefs related to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…However, simply introducing the curricula would be insufficient if the teaching and learning approaches fail to explore active learning involving the community, home, and technological factors. The curricula must also feature multidisciplinary concepts [40,41] that integrate all the mentioned factors before introducing the curricula into the secondary education spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, simply introducing the curricula would be insufficient if the teaching and learning approaches fail to explore active learning involving the community, home, and technological factors. The curricula must also feature multidisciplinary concepts [40,41] that integrate all the mentioned factors before introducing the curricula into the secondary education spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The educational strategies employed were active, interactive, game-based, project-based, experiential, action-based, collaborative, problembased, and multidisciplinary learning strategies (Table 3). The results indicated that the introduction of such content on RE and sustainable development concepts increased the overall interests of the students in RE concepts and STEM subjects, motivated them to learn more about the environmental issues and how to address them, increased their knowledge about RE concepts, and increased their awareness about the necessity of environmental safety and the different strategies for harnessing green and clean environmentally benign energy [20,27,28,30,36,[39][40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the implementation of the Low Carbon School initiative, the school community will be able to adopt a lifestyle that using renewable energy alternatives, involves less dependence on fossil fuels, and adopts "3R" practices of Reuse, Reduce and Recycle. In fact, through this programme, students' literacy can be enhanced through the foundation of this energy-literate education and low carbon practice (Mageswary et al, 2015). A study by John et al (2016) at primary schools around New South Wales, Australia showed that the implementation of the Climate Clever Energy Savers (CCES) programme was effective in helping students to identify ways to reduce electricity consumption and improve their literacy knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive knowledge of students about environmental care is also influenced by family practices, teachers, media, reading practice, and the school curriculum's environmental content (Zarrintaj et al, 2013). In addition, effective teaching approaches can also help to improve the students' levels of environmental energy literacy (Mageswary et al, 2016). The theory of student involvement, developed from Vygotsky (1978) emphasises the role of the environment in students' learning process by encouraging their involvement through the introduction of effective pedagogical practices in the learning process ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%